Exploring different methods for assessing anchorage loss during orthodontic space closure: A narrative review - Ushmita Mehta; C. Munish Reddy; Amit Kumar Khera; Pradeep Raghav; Sukanya Arya; Anusha Jaiswal (Wolters Kluwer Medknow Publications, 2024)
To ensure successful treatment and to prevent undesired tooth movements, it's essential to manage reciprocal forces effectively. Anchorage control becomes particularly crucial in cases involving extractions, where it can help prevent unwanted tooth movement. However, during treatment, there's a risk of anchorage loss, which can undermine the treatment objectives. Therefore, it's imperative to monitor molar movement and assess for anchorage loss throughout treatment. Research publications were searched on search engines such as Scopus, PubMed, and Google Scholar, and articles with terms such as "anchorage management, assessment of anchorage loss, anchorage loss, space closure , en masse retraction and canine retraction" were collected. Various methods for evaluating anchorage loss are dental casts, 3-Dimensional assessment and lateral cephalogram superimposition. Dental casts works well for assessing anteroposterior anchorage loss in maxillary first molars. However, their utility in the mandibular arch is limited due to the absence of a stable reference point. Lateral cephalometry faces the challenge of superimposing bilateral structures. The recent introduction of 3D superimposition techniques offers a potential solution for assessing anchorage loss in the vertical dimension using dental casts.